Capital misallocation and mitigating policies - Dutra, Ana Luiza Perdigão Valadares (2016)
The purpose of this work is to study the role for government in mitigating capital misallocation. We develop an entrepreneurship model in which heterogeneous producers face collateral constraints on production, but can hedge idiosyncratic shocks. Hedging works as a tool for reallocating resources to states in which they are more productively deployed, and can alleviate the effect of the financial frictions and be a counteracting force to capital misallocation. Government incentives to hedging improve workers’ welfare in steady state through an increase in TFP and wages. The intervention leads to a reduction in the rate of return of entrepreneurs and an increase in wealth dispersion. These two effects cause entrepreneurial welfare to decrease.